Volatility Spillovers from Australia's Major Trading Partners across the GFC - David E. Allen; Michael McAleer; Robert J. Powell; Abhay K. Singh (Tinbergen Institute, 2014)
This paper features an analysis of volatility spillover effects from Australia's major trading partners, namely, China, Japan, Korea and the United States, for a period running from 12th September 2002 to 9th September 2012. This captures the impact of the Global Financial Crisis (GFC). These markets are represented by the following major indices: The Shanghai composite and the Hangseng. (in the case of China, as both China and Hong Kong appear in Australian trade statistics), the S&P500 index, the Nikkei225 and the Kospi index. We apply the Diebold and Yilmaz (2009)Spillover Index, constructed in a VAR framework, to assess spillovers across these markets in returns and in volatilities. The analysis confirms that the US and Hong Kong markets have the greatest influence on the Australian one. We then move to a GARCH framework to apply further analysis and apply a tri-variate Cholesky-GARCH model to explore the effects from the US and Chinese market, as represented by the Hang Seng Index.
Keywords: G12; C58; 330; Volatility Spillover Index; VAR analysis; Variance Decomposition; Cholesky-GARCH